KONFLIK KOMUNITAS: ANALISIS FENOMENA GENG PESERTA DIDIK DI SMPN 5 LHOKSEUMAWE - Dedek Dhea Fitriana; Suhaila, Suhaila; Revi Safitri (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
The purpose of this research is to analyze student gang communities, factors that influence student gang communities, the impact of gang communities on academic achievement, and the role of guidance and counseling on student gang communities. This study is of a qualitative type and was carried out using phenomenological techniques. This study was conducted at SMP Negeri 5 Lhokseumawe. Research shows that effective and efficient school policies need to be implemented to overcome the current problem of student gang community conflict. Being involved in a gang community will have a negative impact on students' academic achievement, but by implementing moral values ​​such as honesty, discipline and responsibility, students can be directed towards more positive behavior. The research is expected to be able to provide support and advice to students to continue to comply with school policies, so that schools can adopt relevant policies. This shows that the research not only reaches conclusions but also provides practical suggestions that can be used to develop policies and programs capable of eradicating student gang communities in schools.